THE BAYESIAN NETWORK AS A TOOL SUPPORTING FLOOD RISK MANAGEMENT – AN EXAMPLE OF CULTURAL HERITAGE PROTECTION - Kuźmiński, Łukasz (Economics and Environment, 2016)
The article is dedicated to the subject of the support of the process of flood danger management. The main aim of this study is a presentation of the Bayesian network as a tool for supporting the process of flood risk management. To present how the Bayesian network works the example of the risk assessment for cultural heritage was analysed. In the initial part of this research paper, the following issues are presented: flood, flood risk, risk flood management and fi nancing the fi ght with the effects of a natural disasters. The second part is dedicated to the presentation of Bayesian network for the assessment of the flood risk for the cultural heritage with the detailed description of its nodes.